Information Technology as a Modern Da'wah Media in Indonesia: Prospects and Challenges - Rusli, Rusli (Lembaga Penelitian dan Pengabdian Masyarakat (LP2M) IAIN Langsa, 2023)
The current da'wah media continues to develop along with the development of information technology, this condition poses a challenge for preachers to be careful in choosing da'wah media. Information technology as a digital medium today can be used for various purposes, one of which is as a medium of da'wah, given the rapid development of technology in recent decades. This paper aims to analysis the opportunities and challenges of da'wah in the current era of information technology. This paper is a type of qualitative research with a netnographic approach, this approach aims to examine, observe and observe the use of information technology in preaching. In addition, to strengthen the data in this study, this paper also uses several important articles produced by the researchers. This paper argues that in Indonesia today the use of information technology with various digital media platforms is a priority in preaching, even with digital media making it easier for preachers to convey religious knowledge. Even da'wah through online media is able to reach and influence the whole world without having to meet in person, but the limited internet infrastructure available in remote areas is a separate obstacle.